Health Literacy-Related Knowledge, Attitude, and Perceived Barriers: A Cross-sectional Study among Physicians, Pharmacists, and Nurses in Public Hospitals of Penang, Malaysia - Retha Rajah; Retha Rajah; Mohamed Azmi Hassali; Ching Jou Lim (Frontiers Media S.A., 2017)
IntroductionPatients' health literacy (HL) has emerged as a critical determinant of health outcomes and becoming one of the core competencies of health-care providers. Therefore, this study aimed to assess among Malaysian physicians, pharmacists, and nurses, their HL-related knowledge, attitude, and perceived barriers, and also to determine the associated factors.MethodsA cross-sectional study design was used to enroll 600 eligible respondents using stratified sampling from 6 public hospitals in Penang, Malaysia. A validated self-administered questionnaire was used for data collection. Descriptive and inferential analysis was performed with statistical significance defined as p < 0.05.ResultsThe response rate was 87.6% with 526 questionnaires completed. Of these, 34.2% had poor knowledge, and more than half had negative attitude (51.9%) toward HL with no significant differences among physicians, pharmacists, and nurses. The majority of the respondents perceived time constraints and lack of human resources as major HL barriers. Respondents who had heard the term or concept of HL had significantly higher level of knowledge (p < 0.001) and more positive attitude (p < 0.001). While longer service years (≥11 years) significantly contribute to the higher level of HL knowledge among health-care providers (p = 0.028).ConclusionThe study findings supported the concern on inadequate knowledge and substantially negative attitude toward HL among study health-care providers with highest cited barriers were time constraint and human resources. Thus, efforts to improve their perspective about HL to be effective patient educators are highly advocated.